Bowel movement frequency and risks of major vascular and non-vascular diseases: a population-based cohort study among Chinese adults. Issue 1 (9th January 2020) - Yang, Songchun; Yu, Canqing; Guo, Yu; Bian, Zheng; Fan, Mengyu; Yang, Ling; Du, Huaidong; Chen, Yiping; Yan, Shichun; Zang, Yajing; Chen, Junshi; Chen, Zhengming; et al.
Abstract : Objective: The application of bowel movement frequency (BMF) in primary care is limited by the lack of solid evidence about the associations of BMF with health outcomes apart from Parkinson's disease and colorectal cancer. We examined the prospective associations of BMF with major vascular and non-vascular diseases outside the digestive system. Design: Population-based prospective cohort study. Setting: The China Kadoorie Biobank in which participants from 10 geographically diverse areas across China were enrolled between 2004 and 2008. Participants: 487 198 participants aged 30 to 79 years without cancer, heart disease or stroke at baseline were included and followed up for a median of 10 years. The usual BMF was self-reported once at baseline. Primary and secondary outcome measures: Incident events of predefined major vascular and non-vascular diseases. Results: In multivariable-adjusted analyses, participants having bowel movements 'more than once a day' had higher risks of ischaemic heart disease (IHD), heart failure, chronic obstructive pulmonary disease, type 2 diabetes mellitus and chronic kidney disease (CKD) when compared with the reference group ('once a day'). The respective HRs (95% CIs) were 1.12 (1.09 to 1.16), 1.33 (1.22 to 1.46), 1.28 (1.22 to 1.36), 1.20 (1.15 to 1.26) and 1.15 (1.07 to 1.24). The lowest BMF ('less than three times a week') was also associated with higher risks of IHD, major coronary events, ischaemic stroke and CKD. The respective HRs were 1.07 (1.02 to 1.12), 1.22 (1.10 to 1.36), 1.11 (1.05 to 1.16) and 1.20 (1.07 to 1.35). Conclusion: BMF was associated with future risks of multiple vascular and non-vascular diseases. The integration of BMF assessment and health counselling into primary care should be considered.